Políticas públicas para educação profissional e tecnológica e o mundo do trabalho contemporâneo: um estudo de caso dos egressos dos Cursos Técnicos Integrados do CEFET-MG - Coutinho, Eduardo Henrique Lacerda (2016)
The overall objective of the research is to analyze the Public Policy interrelations for Vocational and Technological Education (VTE), the world of contemporary work, intermediated by the profile of training and professional performance of graduates of integrated technical courses in electronics and electrical engineering from CEFET-MG. The unfolding of the objective occurred into four specific objectives: a) present the Public Policies for VTE and analyze its relationship with the world of contemporary work; b) explain the professional and technological skills required by the capitalist production system in the labor market; c) analyze the interrelationships of public policies for VTE with the training profile of the investigated graduates; and d) correlating the professional skills and the application of technologies required by contemporary capitalist production systems. The reason of this study was legitimized by the shock fought in the institution about labor market from the question: to what extent the training profile of CEFET-MG Integrated Technical Courses are relating to Public Policies for VTE and inserting the graduates in the Contemporary labor market? Concerning the hypotheses, they are supported by assumptions: a) there is not interlocution of VTE Public policy, which prescribes a full and complete training, with the capitalist production system in the contemporary labor market; b) there is an interrelation of VTE Public Policy with the training profile of integrated technical courses of CEFET-MG; and c) there is a partial correlation of the professional performance of the graduates researched that occurs through productionist operational techniques required by the capitalist production system in the contemporary labor market The methodology used was qualitative in nature through the case study method, demonstrated in the documentary sources and online form, which allowed a deepening of this research. The results obtained showed the following opinions: a) although the vast majority of graduates investigated work or are working as high school-level technicians, they chose to attend graduation and post-graduation in related areas of technical education; and b) within the framework of labor market, companies where worked and / or work the surveyed technicians: a) implement centralized management, concentration planning; b) apply the automated technologies of flexible scheduling; c) organize the equipment in cells with operating junction, inspection and maintenance in continuous production flow; and d) the meaning assigned to work permeates the field of productivity, economic bias and the social aspects of productivity. This scenario demonstrates that the option held by the courses graduates, corroborates with the vertical integration of design education - high school-level technical, undergraduate and graduate - CEFET-MG, which allows the institution to keep the discussion with the Ministry of education in consolidating the transformation in Technological University. Finally, the specificities of professional and technological skills related to these technical, gives us a dialogue and interaction with the productive sectors, to improve the designs of integrated technical courses and the implementation of policies for EFA, through the assembly a regional observatory